The Development of Health Behavior of Secondary School Student - Ingkawanich, Kunchasa (Academic Journal of Thailand National Sports University, 2022)
The purpose of this research The development of health behavior of secondary school student 1) To study about the element with the behavior health from the student in the upper secondary school 2) To improve the project with the.behavior health from the student in the upper secondary school 3) To estimate the effect from the project with the behavior health from the student in the upper secondary school and canfind | variable and that is about the behavior health and the variable that can observe has 6 variable in the personality side, technology side, belief side, take action side, attitude side, knowledge side, and the variable that can notice has 24 variable by (Research and Devlopment) and research by (Mixed Methods by Research) and has 3 phase 1) To study about the element with the behavior health of knowledge element from the student in the upper secondary school 2) To improve the project with the.behavior health from the student in the upper secondary school of knowledge element 3) To estimate the effect from the project with the behavior health from the student in the upper secondary school 336 persons from the (Book Matrix Sampling) and analysis the detail by Quantitative with percentage average and analysis model by reason and cheek all the theory by the Lirase program (Version 9.10) the tools that use the project of the behavior health from the student in the upper secondary is be compose of teacher manual paper test, knowledge, student and the evaluate forms in the the behavior health from the student in the upper secondary school project. The results of the research were as follow: The element be composed of the behavior health from the student in the upper secondary school of knowledge element and has 6 element is match with empirical detail the personality sidetechnology sidebelief sidetake actionside, attitude side, knowledge side The construct validity of structural model which analyzed by the exploratory factor analysis showed by the chi-square goodness of fit = 159.57, df = 149, p-value = 0.00000, RMSEA = 0.09, GFI = 0.90, AGFI = 0.81, CFI = 0.97, RMR = 1.12, SRMR = 0.05 ba CN = 145.51